Effects of sintering temperature on physical properties of (K0.5Na0.5)NbO3 ceramics - Hoài Trang, Dụng Thị; An, Hoàng Ngọc; Liên Hương, Lê Thị; Tú, Lê Trần Uyên; Tùng, Võ Thanh (Hue University Journal of Science: Natural Science, 2020)
This paper reports the synthesis of K0.5Na0.5NbO3 (KNN) ceramics by using an improved conventional method. The influence of sintering temperatures of the fabricated ceramics on the piezoelectric and dielectric properties was studied. It was found that density increases greatly within a narrow temperature range, and reaches the highest value of 4.2 g/cm3 at 1090 °C, corresponding to a dense microstructure with the tetragonal grain shape. However, when sintering temperature slightly exceeds the optimal one, the density tends to decrease, accompanied by the appearance of abnormal grain growth, which is considered to be due to the intensified volatilization of alkali metal oxides. At a sintering temperature of 1090 °C, the highest values of electromechanical coupling factor (kp) and the piezoelectric coefficient (d33) of the ceramics being 0.22 and 61 pC/N, respectively, may be related to homogenous grains size of orthorhombic phase.